Imaging the structure of the interface between symmetries interconnected by a discontinuous transition - Fasano, Yanina; de Seta, M.; Menghini, M.; Pastoriza, H.; de la Cruz, F.; Fasano, Yanina (Elsevier, 2003)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina; Universidad Nacional de Cuyo; Argentina